Intrauterine exposure to di(2-ethylhexyl) phthalate (DEHP) disrupts the function of the hypothalamus-pituitary-thyroid axis of the F1 rats during adult life - Sousa-Vidal, Érica Kássia; Henrique, Guilherme; Silva, Renata Elen Costa da; Serrano-Nascimento, Caroline (Frontiers in Endocrinology, 2023)
DEHP is an endocrine disruptor widely used in the production of malleable plastics. DEHP exposure was associated with altered hypothalamic-pituitary-thyroid (HPT) axis function. Although previous studies reported deleterious effects of DEHP exposure during the intrauterine period, few studies have evaluated the direct effects triggered by this endocrine disruptor on the offspring animals' thyroid function. This study aimed to investigate the impact of intrauterine exposure to DEHP on the HPT axis function programming of the offspring animals during adulthood. Pregnant Wistar rats were orally treated with corn oil or corn oil supplemented with DEHP (0.48 or 4.8 mg/kg/day) throughout the gestational period. The offspring rats were euthanized on the 90th postnatal day. Hypothalamus, pituitary, thyroid, and liver were collected to analyze gene expression and protein content through qPCR and Western Blot. Blood was collected to determine TSH and thyroid hormone levels through fluorometric or chemiluminescence immunoassays. In the adult F1 female rats, the highest dose of DEHP decreased TSH serum levels. In the thyroid, DEHP reduced the gene expression and protein content of NIS, TSHR, TG, TPO, MCT8, NKX2.1, PAX8, and FOXE1. These data are consistent with the reduction in T4 serum levels of the F1 DEHP-exposed female rats. In the liver, DEHP exposure increased the mRNA expression of Dio1 and Ttr, while the highest dose of DEHP reduced the mRNA expression of Ugt1a1 and Ugt1a6. Conversely, in the F1 male adult rats, TSHB expression and TSH serum levels were increased in DEHP-exposed animals. In the thyroid, except for the reduced protein content of TSHR, none of the evaluated genes/proteins were altered by DEHP. TH serum levels were not changed in the DEHP-exposed F1 male rats compared to the control group. Additionally, there were no significant alterations in the expression of hepatic enzymes in these animals. Our results demonstrated, for the first time, that intrauterine exposure to DEHP disrupts the HPT axis function in male and female offspring rats and strongly suggest that DEHP exposure increases the susceptibility of the offspring animals to develop thyroid dysfunctions during adulthood.